2017
DOI: 10.1007/s11738-017-2413-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of phytohormones during seed hydropriming and heat shock treatment on sunflower (Helianthus annuus L.) chilling resistance and changes in soluble carbohydrates

Abstract: The objective of this study was to analyze the mechanism of some physiological processes accompanying acquisition of sunflower (Helianthus annuus L.) chilling resistance due to seeds hydropriming in the presence of salicylic acid, jasmonic acid, 24-epibrassinolide followed exposition of seeds to short-term heat shock treatment. The seeds were hydroprimed at 25°C in limited amounts of water or solution of salicylic or jasmonic acid at 10 -2 , 10and 10 -4 M concentration, 24-epibrassinolide at 10 -6 , 10 -8 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Those substances are known as promoters of defense mechanisms against stress (Li et al., 2016). The relationship between the increase in salicylic and jasmonic acid contents and a higher resistance of seeds to extreme temperatures has been reported by Górnik and Lahuta (2017) in sunflower ( Helianthus annuus ) seeds. Moreover, treatment with 24‐EpiBL usually favors increased thermal tolerance in tissues by the accumulation of heat‐shock proteins (Dhaubhadel, Browning, Gallie, & Krishna, 2002) and higher expression of genes involved in tolerance to heat (Dhaubhadel & Krishna, 2008).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Those substances are known as promoters of defense mechanisms against stress (Li et al., 2016). The relationship between the increase in salicylic and jasmonic acid contents and a higher resistance of seeds to extreme temperatures has been reported by Górnik and Lahuta (2017) in sunflower ( Helianthus annuus ) seeds. Moreover, treatment with 24‐EpiBL usually favors increased thermal tolerance in tissues by the accumulation of heat‐shock proteins (Dhaubhadel, Browning, Gallie, & Krishna, 2002) and higher expression of genes involved in tolerance to heat (Dhaubhadel & Krishna, 2008).…”
Section: Discussionmentioning
confidence: 53%
“…The use of 24‐epibrassinolide (24‐EpiBL) for seed priming may promote additional beneficial effects, such as higher antioxidant activity of enzymes in the defense system against reactive oxygen species (ROS; Moori & Eisvand, 2017) and greater seed and/or seedling tolerance to stresses, which include high or low temperatures (Anwar et al., 2018; Górnik & Lahuta, 2017), drought (Shakirova et al., 2016; Tanveer, Shahzad, Sharma, & Khan, 2019), salinity (Tiwari, Kamal, & Prasad, 2016), persistent organic pollutants (Ahammed et al., 2017; Shahzad et al., 2018; Sharma et al., 2016), and hazardous chemical substances including heavy metals (Kohli et al., 2018; Shahzad et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Maximum photochemical efficiency of PSII was estimated by the calculation: F v /F m = (F m - F o )/F m (Kalaji M.H. et al, 2014; Górnik and Lachuta, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Jalink et al (1998) and Górnik et al (2013) indicated that it can be used for assessment of maturation advancement of cabbage and coriander seeds, taking into consideration that their degreening process is directly related with the amount of chlorophyll in seed coats, which was monitored by measuring of maximal efficiency of PSII. Górnik and Lachuta (2017) demonstrated that the changes in maximal photochemical efficiency of PSII (F v /F m ) in sunflower seedlings was related to their growth, which was reduced by previous chilling and increased by subsequent priming of seeds, sown then after these treatments to obtain seedlings subjected to assessments of physiological activity. Chlorophyll fluorescence was also proposed as a marker of the plant reactions to herbicides mechanism of action (Dayan et al, 2012), cellular damage by glyphosate herbicide in Raphanus sativus L. plants (Silva et al, 2014) and it was used in physiological evaluation of strawberry varieties (Żebrowska and Michałek, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the seeds are subject to variations in the temperature conditions at sowing and they can present different physiological and biochemical responses depending on their physiological potential. Sunflower is sensitive to extreme temperatures (high and low), which cause a reduction in the rate and percentage of emergence, seedling growth, disease occurrence, and others (Akladious, 2014;Henning, Ceronio, & Nel, 2017;Górnik & Lahuta, 2017).…”
Section: Introductionmentioning
confidence: 99%